Correlation between estrogen receptor and programmed death ligand-1 in type I endometrial cancer - Setyo Teguh Waluyo; Brahmana Askandar Tjokroprawiro; Anny Setijo Rahaju (Elsevier, 2024)
Objective: To determine the effect of estrogen receptor (ER) on programmed death-ligand 1 (PD-L1) expression in type I endometrial cancer (EC). Material and Methods: This retrospective study included 85 patients with type I EC who underwent surgery at Dr. Soetomo Hospital between 2018 and 2022. A random sampling technique was employed. Immunohistochemistry (IHC) with ER and PD-L1 antibodies was performed on all samples. In this study, ER expression served as the independent variable, while PD-L1 expression was considered the dependent variable. Data analysis was performed using Spearman's rank correlation coefficient test. Results: Out of the 85 patients with type I EC, 58 (68.2%) exhibited positive and 27 (31.8%) exhibited negative ER expression. Meanwhile positive PD-L1 expression was seen in 67 (78.8%) and 18 (21.2%) exhibited negative PD-L1 expression. The study revealed a strong negative correlation between ER and PD-L1 expression in EC (rho value = −0.886, p-value = 0.0001). Conclusion: ER downregulates PD-L1 in type I EC. The findings of this study can be used as reference data and as the basis for further research, especially investigations of the prognostic and immunotherapeutic value of ER and PD-L1 expression in type I EC.